The Construct Validity of the German Academic Self-regulation Questionnaire (SRQ-A) within Primary and Secondary School Children - Kröner, Julia; Goussios, Christina; Schaitz, Caroline; Streb, Judith; Sosic-Vasic, Zrinka (Frontiers in Psychology, 2017)
The assessment of students’ motivation can be a powerful tool in enhancing and understanding students´ learning. One valid and often applied self-report measure is the Academic Self-Regulation Questionnaire (SRQ-A) which is grounded in the self-determination theory. However, to date, there is still no German equivalent to the English version of this questionnaire. Therefore, the aim of the present study was to adapt and validate the SRQ-A on a representative German student sample, consisting of 672 children (327 girls), ages 8 – 14 from one primary and two secondary German schools. First, the translation-back-translation method was used to ensure the linguistic equivalence of the German questionnaire. Second, item analysis of the generated scores of the German SRQ-A were conducted. Third, the multidimensional factorial structure of the original measure was tested with confirmatory factor analysis (CFA) using maximum likelihood estimation. Last, additional construct validity of the German SRQ-A was tested using correlational analyses with convergent and divergent measures. After conducting CFA, four items were excluded from the original questionnaire, due to loadings lower than .40, resulting in 28 items. The German SRQ-A showed good internal consistency for all subscales, with Chronbach´s α ranging between .75 and .88. The simplex-structure of the original measurement could also be confirmed, however, the four-factorial model could not be replicated. The measurement showed good convergent and discriminant validity with other related questionnaires. In summary, the German SRQ-A is a reliable and valid self-report instrument for the assessment of self-determined motivational styles within the school context.